2013
DOI: 10.4103/0019-5049.118558
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexmedetomidine infusion on propofol requirement for maintenance of optimum depth of anaesthesia during elective spine surgery

Abstract: Background:Maintenance of adequate depth of anaesthesia in spine surgery is vital to prevent awareness, to reduce stress response and possible autonomic instability frequently associated with spine surgery. Dexmedetomidine, a α2-adrenoceptor agonist with analgesic and sedative adjuvant property has been found to reduce dose requirement of multiple anaesthetic agents both for induction and during the maintenance of anaesthesia.Aim:The aim of this study is to observe the effect of dexmedetomidine, on the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…The mean dose of propofol needed for induction was reduced significantly by 43.01% in the patients receiving dexmedetomidine. This finding was in consistent with the study done by Suvadeep Sen et al 19 . who studied the effect of dexmedetomidine infusion on propofol requirement for maintenance of optimum depth of anaesthesia during elective spine surgery and concluded that requirement of propofol at induction and during maintenance was lessened by 48.08% and 61.87% respectively and dose was calculated maintaining bispectral index between 40 and 60 (p<0.05).…”
Section: Fig3 Discussionsupporting
confidence: 83%
“…The mean dose of propofol needed for induction was reduced significantly by 43.01% in the patients receiving dexmedetomidine. This finding was in consistent with the study done by Suvadeep Sen et al 19 . who studied the effect of dexmedetomidine infusion on propofol requirement for maintenance of optimum depth of anaesthesia during elective spine surgery and concluded that requirement of propofol at induction and during maintenance was lessened by 48.08% and 61.87% respectively and dose was calculated maintaining bispectral index between 40 and 60 (p<0.05).…”
Section: Fig3 Discussionsupporting
confidence: 83%
“…Therefore we demonstrated that intranasal dexmedetomidine reduced the propofol requirement during termination of first trimester pregnancy of suction evacuation. Our result was also consistent with other previous studies that dexmedetomidine might reduce the anesthetic dosages [8,9,23]. Guan et al showed that the mean consumption of propofol for termination of first trimester pregnancy of suction evacuation was 3.56 ± 0.98 mg/kg for propofol and 2.11 ± 1.08 mg/kg for propofol combined with sulfentanil5.…”
Section: Discussionsupporting
confidence: 82%
“…[15] A study done by Suvadeep Sen et al have shown a 48.08%dose reduction of propofol induction dose in patients who received dexmedetomidine before induction of anaesthesia. [16] Our results have shown a 50.6% reduction in propofol dose for induction after receiving dexmedetomidine infusion. In our study, it was found that mean induction dose of propofol was significantly lower in group A 67±13.67mg as compared to group B 126±14.73 mg that is statistically significant [p<0.05%].…”
Section: Parametermentioning
confidence: 64%